Sexual Violence Experience Among Nigerian Girls and Young Women: What Are the Roles of Early Sexual Debut, Multiple Sex Partnerships, and Traditional Gender Role Beliefs? - De Veauuse Brown, Natasha F. (Journal of interpersonal violence, 2022)
In Nigeria, one in four females has experienced some form of sexual abuse. Therefore, it is imperative to examine risk factors associated with sexual violence victimization of Nigerian girls and young women to identify targets for prevention and help stakeholders prioritize response efforts. The present article focuses on secondary data analyses of 1,766 females, aged 13 to 24, interviewed in the population-based 2014 Nigeria Violence Against Children Survey. The outcome of interest is lifetime sexual violence (LSV). Several potential predictors were explored: beliefs about gender roles related to sex, early sexual debut (aged <16 years), and multiple sex partners in the past 12 months. Other risk factors assessed were age, ethnicity, religion, education, marital status, and employment. Logistic regression analyses estimated adjusted odds ratios (AORs) with 95% confidence intervals (CIs). Results revealed that females who endorsed beliefs about patriarchal sexual decision-making (AOR = 2.1, 95% CI = [1.28, 3.32]) or ever attended school (AOR = 2.4, 95% CI = [1.35, 4.34]) were more likely to report experiencing LSV. Prevention programs that target traditional norm beliefs about gender and sexuality have the potential to influence sexual violence in Nigeria. In addition, school attendance may expose females to potential perpetrators. Thus, to prevent sexual violence of girls who attend school, implementing safety measures may be beneficial for protecting them while in and traveling to/from school.